2023
DOI: 10.1097/nmd.0000000000001613
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Behavioral Therapy for Insomnia for the Treatment of Child and Adolescent Anxiety and Depression

Abstract: Cognitive behavioral therapy for insomnia (CBT-I) has shown promising results in the adult population. However, there is not enough evidence for children and adolescents. Hence, we evaluated the current evidence of CBT-I in the treatment of anxiety and depression in children and adolescents. Published randomized clinical trials published before June 2020 were searched from PubMed, Cochrane Library of database, clinicaltrials.gov, and Google Scholar. Out of seven included studies, six studies assessed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…By treating cognitive symptoms and deficits, enhancing stress management, and improving sleep architecture to reduce limbic activation, improve prefrontal regulation, and reduce mid–limbic brain dysregulation as well as better cortisol reactions to stress and inflammatory cytokine regulation, CBT reduces the symptoms of insomnia and comorbid mental health disorders, including anxiety and depression ( 103 ). Therefore, CBT can effectively improve depression and anxiety in adolescents with adolescent insomnia through mental health education, cognitive restructuring, and mental and physical relaxation techniques ( 104 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…By treating cognitive symptoms and deficits, enhancing stress management, and improving sleep architecture to reduce limbic activation, improve prefrontal regulation, and reduce mid–limbic brain dysregulation as well as better cortisol reactions to stress and inflammatory cytokine regulation, CBT reduces the symptoms of insomnia and comorbid mental health disorders, including anxiety and depression ( 103 ). Therefore, CBT can effectively improve depression and anxiety in adolescents with adolescent insomnia through mental health education, cognitive restructuring, and mental and physical relaxation techniques ( 104 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 meta-analysis by Oud et al demonstrated CBT's effectiveness for youth with depression ( Oud et al, 2019 ). Similarly, a review conducted by Reddy et al highlighted the robust impact of CBT on depressive symptoms among adolescents ( Reddy et al, 2023 ). Despite these effective interventions, most adolescents with mental health needs do not receive adequate treatment ( Essau, 2005 ; Mojtabai et al, 2016 ; Merikangas et al, 2011 ).…”
mentioning
confidence: 99%